Konsep Kepemimpinan Dari Perspektif Perjanjian Lama: Kisah Daud (Jurnal Pendidikan Agama dan Teologi, 2023)
Leaders are people who can be entrusted with leadership, not just anyone, but people who really have a leadership spirit because we can see from Bible figures in the Old Testament like "David" is a shop that people often talk about. In this writing, the author will explain what David's leadership means in relation to the text of the Old Testament. The Bible and reference books are used in qualitative methods to apply. this study finds that the leadership of "David" is an example for everyone in terms of leadership. And all thank God for the goals he achieved.